The case for a European-wide strategy - Jean Dermine (EIB Papers, 1999)
Although a large series of papers have been concerned with macroeconomic issues such as price stability or employment, very few studies have discussed the impact of the euro on the competitive structure of European banking markets. Two questions are being addressed in this paper: How does the move from national currencies to the euro alter the sources of competitive advantage of banks? What are the main strategic options available to financial firms? A review of the European banking industry shows the apparent importance of a national currency. For instance, the markets for pension funds and mutual fund management, or the euro-francs and euro-guilder bond markets are quite fragmented with domestic institutions capturing a very large market share. This paper shows how, besides an obvious loss of intra-European currencies trading business, the introduction of a common currency changes fundamentally the sources of competitive advantage of banks. Clearly, this calls for a major review of strategic options. The paper is structured in two parts. Drawing on research discussed in an earlier EIB Papers article, the first section summarises a number of impacts of the euro (1). In the second part, the strategic options are outlined.
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Euro; Bank; Wettbewerb; Arbeitsorganisation; EU-Staaten